The centrifugal-centripetal continuum : towards a consummation-oriented ambivalent answerability in a Bakhtinian reading of Faulkner's As I Lay Dying and Radcliffe's The Romance of the Forest - Behnam, Aydin (2010)
It can be argued that the most pivotal legacy of Mikhail Bakhtin is the term ―Dialogism‖. However the non-preference of centralising and de-centralising forces over each other with which Dialogism is implicated has been used by many, including the poststructuralists, to suit their own purpose of attributing chaos to dialogue. Thus the voices in the text have been left dangling so to speak and have not been tied up to any ends because the readers are often afraid to speak of finalisation when it comes to Dialogism. In addition, it is peculiar that it is hard to come across an in-depth analysis of the treatment of the notions of ―centrifugal‖ and ―centripetal‖ where these notions are at the core of Bakhtin‘s discussions on finalisation. Therefore the attempt of this thesis is to come up with a way of understanding what this consummation or finishing off of voices or forces may mean and also to see what effect this consideration will have on the theoretical and practical sphere of a Bakhtinian analysis of a text.